PELATIHAN SIKLUS AKUNTANSI BAGI SISWA/I SMK RAHMANI DALAM RANGKA PENINGKATAN LITERASI KEUANGAN - Ferry Adang; Amin Wijoyo; Adrian Martinus Hartono; Ferdi (Jurnal Serina Abdimas, 2026)
The declining interest in accounting majors at the university level has become a significant concern that must be addressed early through secondary education initiatives. One such effort was carried out through a Community Service (PKM) program focusing on enhancing students’ financial literacy. This activity was conducted by lecturers and students from the Faculty of Economics and Business, Tarumanagara University, at SMK Rahmani Jakarta, with the objective of improving students’ understanding of the accounting cycle. The training was delivered face-to-face for two hours, involving 20 students as participants. The method consisted of a pre-test, material presentation, interactive quiz using the Kahoot platform, and a post-test to measure learning improvement. The training materials covered basic accounting concepts, stages of the accounting cycle, and their application in financial statement preparation. The results showed that 65% of students answered the quiz questions correctly, indicating a noticeable improvement in comprehension and knowledge. In addition to cognitive enhancement, the activity fostered enthusiasm for learning and developed students’ character traits such as discipline, accuracy, and responsibility. This program demonstrated that an interactive and technology-based approach can create an engaging and effective learning experience in accounting education at the vocational school level. In the future, similar activities are recommended to be implemented continuously with more practical sessions and inter-institutional collaboration to strengthen students’ readiness for higher education and the professional world. Penurunan minat terhadap jurusan akuntansi di tingkat perguruan tinggi menjadi isu penting yang perlu diatasi sejak jenjang pendidikan menengah. Salah satu upaya yang dilakukan adalah melalui kegiatan Pengabdian Kepada Masyarakat (PKM) yang berfokus pada peningkatan literasi keuangan siswa. Kegiatan ini dilaksanakan oleh tim dosen dan mahasiswa Fakultas Ekonomi dan Bisnis Universitas Tarumanagara di SMK Rahmani Jakarta dengan tujuan meningkatkan pemahaman siswa terhadap siklus akuntansi. Pelatihan dilakukan secara tatap muka selama dua jam dengan melibatkan 20 siswa sebagai peserta. Metode yang digunakan mencakup pre-test, penyampaian materi, kuis interaktif berbasis platform Kahoot, serta post-test untuk mengukur peningkatan pemahaman peserta. Materi pelatihan meliputi konsep dasar akuntansi, tahapan siklus akuntansi, dan penerapannya dalam penyusunan laporan keuangan. Hasil kegiatan menunjukkan bahwa 65% siswa mampu menjawab pertanyaan dengan benar, menandakan adanya peningkatan pengetahuan dan pemahaman terhadap materi yang disampaikan. Selain meningkatkan kompetensi kognitif, kegiatan ini juga menumbuhkan antusiasme belajar dan membangun karakter disiplin, teliti, serta bertanggung jawab pada siswa. Program ini membuktikan bahwa pendekatan interaktif berbasis teknologi mampu menciptakan pengalaman belajar yang menarik dan efektif dalam pembelajaran akuntansi di tingkat SMK. Ke depan, kegiatan serupa disarankan untuk dilakukan secara berkelanjutan dengan melibatkan lebih banyak sesi praktik dan kolaborasi antarlembaga pendidikan guna memperkuat kesiapan siswa menghadapi dunia kerja.